The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1603/0022-0493-98.4.1187
|View full text |Cite
|
Sign up to set email alerts
|

<I>Uraba lugens</I> (Lepidoptera: Nolidae) in New Zealand: Pheromone Trapping for Delimitation and Phenology

Abstract: A synthetic sex pheromone trapping survey of the leaf skeletonizer Uraba lugens Walker (Lepidoptera: Nolidae) demonstrated the unexpectedly widespread distribution of the insect across > 40,000 ha of urban Auckland, New Zealand. A survey of eucalyptus trees planted in parks and other public areas showed a significant spatial correlation between trap catch and breeding populations, validating the trap survey results. Traps in trees showing damage had four-fold higher catches than traps placed in undamaged or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…This species, native to Australia, invaded into New Zealand around 1995 and is now well established in the northern area of New Zealand (Suckling et al, 2005). Some other non-eucalypt tree species including the unrelated Betula pendula Roth (Betulaceae) and Liquidambar have also been identified as 'novel hosts' in New Zealand although being utilized only occasionally (Berndt unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…This species, native to Australia, invaded into New Zealand around 1995 and is now well established in the northern area of New Zealand (Suckling et al, 2005). Some other non-eucalypt tree species including the unrelated Betula pendula Roth (Betulaceae) and Liquidambar have also been identified as 'novel hosts' in New Zealand although being utilized only occasionally (Berndt unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…An estimate of rates of spread and changes in the distribution range from the initial point of infestation of the non-indigenous insect pest is an essential part of the pest management process. To enable the detection, and to monitor rates of spread, particularly of non-indigenous Lepidopteran pests, pheromone traps have typically been used with a considerable degree of success (Myers & Hosking, 2002;Sharov et al ., 2002;Suckling et al ., 2005;Tobin et al ., 2007). One of the key factors that often influences trap capture rates is the positioning of the trap in the tree canopy (Cardé & Elkinton, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…(2003) note that traps were more efficient at capturing male OPM when placed at this height in the upper canopy, and were less efficient when placed at 2 or 6-8 m. Studies on pine processionary moth (PPM), a close relative of OPM, have also shown that higher numbers of adult males are captured when pheromone traps are placed in the crowns of pine trees (Einhorn et al ., 1983;Jactel et al ., 2006). For many other Lepidoptera species as well, pheromone trap catches are greater when the traps are placed in the upper part of the tree canopy (Sower & Daterman, 1977;Hanula et al ., 1984;Liebhold & Volney, 1984;Bhardwaj & Chander, 1992;Barrett, 1995;Suckling et al ., 2005;Kovanci et al ., 2006). The present study indicated that male OPM captures in traps did not reach a maximum, and continued to rise with an increasing height positioning of the pheromone trap in the canopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pheromone baited traps are widely used for biosecurity surveillance to detect new incursions of unwanted organisms, and to delimit their ranges (Augustin et al., 2004; Suckling et al., 2005a,b; Bogich et al., 2008; Liebhold & Tobin, 2008). They have been used for several decades in pest management for monitoring to alert land managers to the presence of a pest in time and space, providing insight into phenology as well as geographic distribution (Suckling et al., 2005b). Pheromone traps have also been used to delimit populations for pest risk modelling (Kriticos et al., 2007).…”
Section: Introductionmentioning
confidence: 99%